Book Review for Assessments for Inclusion in Higher Education - Promoting Equity and Social Justice in Assessments (Global Journal of Human-Social Science, 2024)
This review examines Inclusive Assessment in Higher Education Promoting Equity and Social Justice in Assessment edited by Rola Ajjawi Joanna Tai David Boud and Trina Jorre De St Jorre The book comprising 21 standalone chapters from 35 contributors explores inclusivity in higher education assessments through societal institutional and interpersonal perspectives It emphasizes the need for assessment practices that cater to diverse student populations considering factors beyond traditional demographics The review highlights the book s strengths including its multi-author approach practical examples and incorporation of indigenous knowledge However it also notes weaknesses such as a lack of field-specific guidelines and limited practical narratives The book contributes significantly to assessment literature offering valuable insights for researchers educators and policymakers seeking to develop more inclusive assessment practices in higher education This review analyzes the book s main arguments strengths weaknesses and potential audience providing a comprehensive overview of its content and relevance in the field of educational assessment
Keywords: higher education assessments; inclusion; book review